Implications of the new regulations for psychiatric health services - Annemarie M Bruwer (AOSIS, 1985)
The theme Ringing in the changes is very apt for there are many changes in the nursing profession. This trend is however much more extensive in SA - change is taking place at a tremendous tempo and at nearly all levels of life, such as constitutional developments and rationalisation of the state departments. In view of this it is of particular importance that the nursing profession has chosen to do self-evaluation at this time and is therefore participating in this process of change.